2019
DOI: 10.12688/gatesopenres.13003.1
|View full text |Cite
|
Sign up to set email alerts
|

Good sex matters: Pleasure as a driver of online sex education for young people

Abstract: Background There are few documented examples of online sex education platforms that make an impact on young people’s sexual health and wellbeing, yet research shows that new media has enormous potential to be harnessed in this way. The same is true for a pleasure-positive approach to sex education curricula and programmes. This research provides empirical evidence from the Love Matters' websites in Mexico, Kenya, Nigeria, Egypt, and India to highlight the prevalence and importance of talking about pleasure-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…At global and national levels, we must improve population-based surveys (e.g., the Demographic and Health Surveys 16 ) so that they collect relevant and appropriate data (e.g., by extending to 10-to 14 year-olds and including boys and young men) while tapping into a wider range of data sources (e.g., metadata from search engines or social media) to attain data that are not collected through large surveys [115,117]. For example, analyses of data from Love Matters 17 through Google Analytics have allowed researchers to better understand young people's interest in and engagement with information about sexual pleasure in Egypt, Kenya, India, Mexico, and Nigeria [118].…”
Section: What Strategic and Specific Actions Mustmentioning
confidence: 99%
“…At global and national levels, we must improve population-based surveys (e.g., the Demographic and Health Surveys 16 ) so that they collect relevant and appropriate data (e.g., by extending to 10-to 14 year-olds and including boys and young men) while tapping into a wider range of data sources (e.g., metadata from search engines or social media) to attain data that are not collected through large surveys [115,117]. For example, analyses of data from Love Matters 17 through Google Analytics have allowed researchers to better understand young people's interest in and engagement with information about sexual pleasure in Egypt, Kenya, India, Mexico, and Nigeria [118].…”
Section: What Strategic and Specific Actions Mustmentioning
confidence: 99%
“…Lessons from previous chatbot studies underscore the importance of continuous review and improvement of content to address diversified and ever-shifting informational needs and other user curiosities. 34 , 35 Of direct relevance for chatbot development, studies have shown that user engagement is enhanced when technology is simple and with sufficient features to encourage feedback loops and timely integration of user-stated needs. 9 , 14 While our version of the chatbot was based on a decision tree with predetermined branching options and content, with advances in artificial intelligence-powered technology, chatbots are leveraging natural language processing and machine learning approaches for enhanced human-like interactions between the user and the chatbot.…”
Section: Discussionmentioning
confidence: 99%